Penerapan Pupuk Mikotricho (Mikoriza-Trichoderma) dan Pupuk Sintetik Pada Budidaya Cabai Merah - Rokhminarsi, Eny; Utami, Darini Sri; Begananda (Jurnal Hortikultura Indonesia, 2019)
The aim of the study was to determine the optimal dosage of mycotricho fertilizer and the reduction dosage of synthetic fertilizer for growth and yield of red pepper on marginal land. The study was conducted from March to September 2018 on the ultisol soil in Kaliori village, Kalibagor sub-district, Banyumas district. The experiment used a Randomized Completely Block Design with 3 replications. The first factor was the dose of mycotricho i.e without mycotricho, 10 g mycorrhizae+10 g Trichoderma, and 20 g mycorrhizae + 20 g Trichoderma. The second factor was the reduction of recommended synthetic fertilizer dosage i.e 0% (recommended dose=SP-36 480 kg ha-1 was converted to SP-27 640 kg ha-1, ZA 320 kg ha-1, urea 240 kg ha-1, 320 kg ha-1 KCl), reduction of 25% and 50%. Data were analized with ANOVA and Duncan's multiple range test 5%. The results showed (1) the application of mycotricho to 40 g (20 g mycorrhizae + 20 g Trichoderma) plants-1 can increase growth and yield of red pepper, (2) reduction of urea, ZA, SP27 and KCl up to 25% of recommended dosage showed better growth and yield of red pepper than recommended dosages, (3) application of 40g mycotricho (20 g mycorrhizae + 20 g Trichoderma) with 25% reduction synthetic fertilizer gave growth to the optimal number of leaves, leaf area, and number of branches and increased yield of red pepper (15.4 t ha-1) of 22.2% compared to without mycotricho at recommended doses (12.6 t ha-1). Application of 20 g mycotricho (10 g mycorrhizae + 10 g Trichoderma) and 25% reduction of synthetic fertilizer increased of yield 15.8% (14.6 t ha-1) compared to without mycotricho and the recommended dosage of synthetic fertilizer.Keywords: biofertilizer, biopesticide, cultivation, vegetables